Altered saccadic targets when processing facial expressions under different attentional and stimulus conditions. (April 2017) - Boutsen, Frank A.; Dvorak, Justin D.; Pulusu, Vinay K.; Ross, Elliott D.
Highlights: Facial blends occur when different emotions are expressed on the upper and lower face. Perception is biased to lower face; if attention is directed to upper face, left visual field becomes biased to upper face. With no attentional instructions, initial saccades target the lower face equally. If attention is directed to the upper face, saccades target the upper face equally. Initial saccades do not completely explain asymmetric attentional-perceptual biases. Abstract: Depending on a subject's attentional bias, robust changes in emotional perception occur when facial blends (different emotions expressed on upper/lower face) are presented tachistoscopically. If no instructions are given, subjects overwhelmingly identify the lower facial expression when blends are presented to either visual field. If asked to attend to the upper face, subjects overwhelmingly identify the upper facial expression in the left visual field but remain slightly biased to the lower facial expression in the right visual field. The current investigation sought to determine whether differences in initial saccadic targets could help explain the perceptual biases described above. Ten subjects were presented with full and blend facial expressions under different attentional conditions. No saccadic differences were found for left versus right visual field presentations or for full facial versus blend stimuli. When asked to identify the presented emotion, saccades were directed to the lower face. When asked to attend to the upper face, saccades were directed to the upper face. When asked to attend to the upper face and try to identify the emotion, saccades were directed to the upper face but to a lesser degree. Thus, saccadic behavior supports the concept that there are cognitive-attentional pre-attunements when subjects visually process facial expressions. However, these pre-attunements do not fully explain the perceptual superiority of the left visual field for identifying the upper facial expression when facial blends are presented tachistoscopically. Hence other perceptual factors must be in play, such as the phenomenon of virtual scanning.